The encoded image (REVISTA NODO, 2025)
The exhibition The Coded Image, by Chema Palacios and the Interspecifics collective —Leslie García, Paloma López, Emmanuel Anguiano, Alfredo Lozano, and Felipe Rebolledo—, curated by Maika Vera Domínguez, was presented at Patricia Conde Galería (Mexico City) from June 8 to July 17, 2024, where pieces from the first formal iteration of the research and artistic creation project All hail [ ] who shall be [ ] hereafter were exhibited. This project explores visual production through neural networks and generative models, as well as its possible interactions with the performing arts and literary narrative as forms of aesthetic exploration and poetic production.
Keywords: Art; Photography; AI; neuroscience; Generative models